Bridging climate action and food systems: Reflections from the 16th FABLE Consortium meeting in Istanbul - Diaz, Maria (2025)
The 16th FABLE Consortium meeting in Istanbul explored how food and land-use models can better inform climate policy amid rising global uncertainty. Discussions centered on strategies to bring scientific evidence into policy debates, innovations to make FABLE tools more accessible to stakeholders, and new methods to better quantify trade spillovers. FABLE members explored ways to make future pathways more politically grounded, inclusive, and responsive to emerging challenges.